PENGARUH KECAKAPAN MANAJERIAL, KOMITE AUDIT DAN LEVERAGE TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2021-2023) - Ulandari, Meli; Basir, Basri; Wahyuni, Wahyuni (LPPM - STIE SAKTI ALAM KERINCI, 2025)
This research aims to determine the effect of managerial competence, audit committee, and leverage on earnings management in manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange. The type of research used is quantitative research with an explanatory research approach. The research sample was obtained using purposive sampling method with a total of 36 companies over three years of observation, resulting in a total of 108 data observations. The dependent variable in this study is earnings management, measured using the Modified Jones model, while the independent variables include managerial competence measured by Data Envelopment Analysis (DEA), the number of audit committee members, and leverage measured by the ratio of total debt to total assets. Data analysis was conducted using multiple linear regression with the help of SPSS version 25. The results of this study show that managerial competence and the audit committee have a positive and significant effect on earnings management. Meanwhile, leverage does not have a significant effect on earnings management. These findings imply that improving managerial competence and the effectiveness of the audit committee can influence earnings management practices in companies, while leverage levels are not always a key driving factor. Keywords: Managerial Competence, Audit Committee, Leverage Earnings Management